Impression Management in Online Identity Formation: A Case Study on Dea Anugrah on Social Media Instagram: Manajemen Kesan Dalam Pembentukan Identitas Daring : Studi Kasus Pada Dea Anugrah di Media Sosial Instagram - Septian, Yusuf; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
The development of information and communication technology has changed the dynamics of social identity online, with social media becoming the main platform for sharing information and interacting. This phenomenon encourages individuals to build online identities that reflect who they are, what they believe, and how they want to be recognised by their audiences. One example of a public figure active in the world of literature and media is Dea Anugrah, a writer and content creator who uses social media, particularly Instagram, to shape and manage her online identity. Based on the theory of impression management (dramaturgy) developed by Erving Goffman, this analysis explores how Dea Anugrah utilises Instagram to build her image as a writer, podcast host, and documentary host. In the front stage phase, she intentionally uploads content that is relevant to her audience, while in the back stage phase, she carefully prepares the content before it is published. The results of the analysis show that Dea Anugrah successfully uses Instagram features to manage her online identity effectively, with planned content and collaboration with other figures to expand her reach. Suggestions for her future online identity management include content diversification, increased interaction with audiences, and more careful privacy management to keep personal data safe. Highlights: Impression Management: Dea Anugrah strategically curates her Instagram content to shape her identity as a writer, podcast host, and documentary presenter, aligning with Goffman’s dramaturgy theory. Content Strategy: She effectively uses planned posts, collaborations, and platform features to expand her audience reach and maintain engagement. Future Improvements: Recommendations include diversifying content, enhancing audience interaction, and strengthening privacy management to protect personal data. Keywords: Social Media, New Media, Personal Branding, Instagram